SCIENTIFIC ARTICLE WRITING TRAINING FOR HIGH SCHOOL ECONOMICS MGMP TEACHERS IN BOJONEGORO REGENCY: PELATIHAN PENULISAN ARTIKEL ILMIAH BAGI GURU MGMP EKONOMI SMA DI KABUPATEN BOJONEGORO - Diah Dinaloni; Fahimul Amri; Henky Muktiadji (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The issuance of Minister of State Apparatus Utilization and Bureaucratic Reform regulation No. 16 of 2009 concerning functional positions of teachers and their credit scores requires teachers who wish to be promoted as of October 2013 to carry out ongoing professional development activities in the form of writing scientific essays and publishing their scientific work. Unfortunately, not all public or private teachers know the procedures and rules for making good writing that can fit in a journal that has a minimum ISSN. For some teachers, scientific work is an obstacle in various ways. Even though the ability to write scientific papers is a must for a professional teacher, both in career advancement and in increasing knowledge and intellect that a teacher must have in the learning process. This PkM aims to increase teachers' knowledge and understanding of scientific articles, assist teachers in writing and publishing scientific articles in national or international journals. This PkM is divided into several methods, namely (1) the preparation stage, which begins with preparing all training needs in the form of training materials and other equipment that supports the training and discusses the schedule for implementing activities and detailed job descriptions for each member of the PkM team; (2) The implementation stage, which includes the schedule for implementing activities and the information delivery stage, where the material presented is general and theoretical in nature. The results of the implementation of PkM for SMA Economics MGMP teachers in Bojonegoro Regency were concluded to be successful. This is indicated by 90% of participants feeling the benefit of participating in this scientific article writing training. The result of this dedication is that participants understand the importance of writing scientific articles, and are able to publish their articles in reputable journals